PROCESS TYPES ON STUDENTS’ PERSUASIVE TEXT: A SYSTEMIC FUNCTIONAL LINGUISTICS STUDY - Sari, Puspita; Gunawan, Hero; CM Simatupang, Ervina (Lire Journal (Journal of Linguistics and Literature), 2024)
This research is entitled Process Types on Students' Persuasive Text: A Systemic Functional Linguistics Study. The purpose of this research is to find out (1) what types of transitivity processes are found in student persuasion texts; and (2) what processes appear most dominant in the text. The theory used in this research is the Systemic Functional Linguistics (SFL) theory which refers to the thinking of Halliday (2014). The research method used is a qualitative descriptive method. The data obtained was based on the results of students' persuasive writing with the title "How to keep ourselves healthy inside and outside". The research results showed that there were 5 types of processes found, namely Material Process (36,7%), Relational Process (23,5%), Mental Process (17,6%), Behavioral Process (14,7%) and Existential Process (7,3%). There was no verbal process found in the persuasive text. Of the five processes, material process is the type of process that appears most dominantly.